A reproducible POI recommendation framework: Works mapping and benchmark evaluation. Issue 108 (September 2022) - Werneck, Heitor; Silva, Nícollas; Pereira, Adriano; Carvalho, Matheus; Bellogín, Alejandro; Martinez-Gil, Jorge; Mourão, Fernando; Rocha, Leonardo
Abstract: This work is a companion reproducibility paper that presents a framework to reproduce our previous experiments and results reported in Werneck et al. (2021). In that previous paper, we introduced a systematic mapping process of points-of-interest (POI) recommendation methods and provided a uniform evaluation methodology based on metrics covering different aspects besides accuracy. Due to the lack of reproducible and extensible benchmarks, our work introduces a reproducibility framework for POI methods based on a collection of Python software libraries and a Docker image. Our proposal is composed of: (1) a package to perform a protocol that reproduces our systematic mapping process Werneck et al. (2021), containing all collected data, insightful views on current advances and opened challenges; and (2) an extensible benchmark to perform a protocol to reproduce experimental evaluations on POI recommendation, considering different datasets, metrics, and the strongest baselines in the literature. This work also demonstrates all processes required to instantiate its framework. Moreover, our work can be considered at least weakly reproducible, since we were able to reproduce the results of the previous paper, leading us to the same conclusions. Highlights: A companion reproducibility paper about POI recommendation. An extensible benchmark about POI recommendation. A collection of Python software libraries and a Docker image. A package to perform a protocol that reproduces our systematic mapping process. A detailed reproducibility analysis of the primary work.